Suspension stabilizing material and preparation and application thereof
By preparing a suspension stabilizing material R1-C-R2-N-R3-R4 with a specific structure, the problem of suspension stabilizing materials failing at high temperatures in the prior art was solved, achieving a suspension effect that does not thicken at low temperatures and does not dilute at high temperatures, making it suitable for cement slurry systems in deep wells and high-temperature blocks.
Patent Information
- Application Number
- CN202411294552.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-07
AI Technical Summary
In existing technologies, suspension stabilizing materials cannot effectively maintain suspension under high temperature conditions, and therefore cannot meet the application requirements of deep wells and blocks with high geothermal gradients.
A suspension stabilizer with a specific structure, R1-C-R2-N-R3-R4, was prepared by dissolving acrylamide-2-methylpropanesulfonic acid, N,N-dimethylacrylamide, methyldiallylammonium chloride, and methylmaleic acid in water, adding an initiator, and adjusting the pH value to carry out a polymerization reaction. This process produced a suspension stabilizer that does not thicken at low temperatures and does not dilute at high temperatures.
It can maintain good suspension stability even at temperatures above 200℃. The density difference of the suspension stabilized material in cement slurry is less than 0.03 g/cm3, which meets the requirements for use in deep wells and high-temperature blocks.
Abstract
Description
Technical Field
[0001] The invention relates to a suspension stable material and a preparation method and application thereof. Background Art
[0002] Deep and ultra-deep oil and gas have become an especially important replacement energy source in China, and there are more and more ultra-deep wells. The quality of the wellbore is directly related to the success or failure of the drilling project and the life of the oil and gas wells. Cementing is a key technology to ensure the quality of well engineering, and cement slurry is the core technology of cementing. It is an important means to ensure the sustainable and high-quality development of oil and gas field exploration and development. Although there are more and more types of high-temperature resistant cement admixtures for cementing, there are very few ultra-high temperature resistant materials in most cementing pre-fluids and cement slurry systems. At present, the industry still uses powdered bio-colloid as a suspension stabilization material. The maximum temperature resistance of colloidal materials is lower than 150°C, and they cannot be used in deep wells and blocks with high geothermal gradients. Therefore, it is urgent to develop a high-temperature resistant suspension stabilization material that can be used in the above blocks. Summary of the invention
[0003] The present invention is made in order to further improve the suspension effect of drilling cement drilling fluid and increase stability.
[0004] As one aspect of the present invention, it relates to a suspension stabilizing material, whose structural formula is R1-C-R2-N-R3-R4, wherein R1 is SO3Na, NH3Cl, CH2CH3 or COONa; R2 is C=O, CH2CH3, C=C or NH3Cl; R3 is COONa, C=O, NH3Cl or C=C; R4 is NH3Cl, SO3Na or COONa; among R1, R2, R3 and R4, only one is NH3Cl, SO3Na or COONa. In a preferred embodiment, R1 is COONa; R2 is NH3Cl; R3 is C=C; R4 is SO3Na.
[0005] As another aspect of the present invention, it relates to a method for preparing a suspended stable material, comprising:
[0006] After 30-40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 4-13 parts of N,N-dimethylacrylamide, 9-17 parts of methyldiallylammonium chloride and 3-8 parts of methylmaleic acid are fully dissolved in water, 3-6 parts of initiator are added, the pH is adjusted to 4.0-9.0, and the reaction is carried out at 50-60 degrees Celsius.
[0007] In certain feasible embodiments, the method comprises:
[0008] After 30-40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 4-10 parts of N,N-dimethylacrylamide, 9-17 parts of methyldiallylammonium chloride and 3-8 parts of methylmaleic acid are fully dissolved in water, 3-5 parts of initiator are added, the pH is adjusted to 6.0-8.0, and the reaction is carried out at 50-60 degrees Celsius.
[0009] In certain feasible embodiments, the method comprises:
[0010] After 30-40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 5-13 parts of N,N-dimethylacrylamide, 9-17 parts of methyldiallylammonium chloride and 3-8 parts of methylmaleic acid are fully dissolved in water, 3-6 parts of initiator are added, the pH is adjusted to 4.0-9.0, and the reaction is carried out at 50-60 degrees Celsius.
[0011] In certain feasible embodiments, the method comprises:
[0012] After 30-40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 5-10 parts of N,N-dimethylacrylamide, 9-17 parts of methyldiallylammonium chloride and 3-8 parts of methylmaleic acid are fully dissolved in water, 3-5 parts of initiator are added, the pH is adjusted to 6.0-7.0, and the reaction is carried out at 50-60 degrees Celsius.
[0013] In some feasible embodiments, the initiator is potassium persulfate, sodium persulfate or ammonium persulfate.
[0014] As another aspect of the present invention, it relates to a suspended stable material prepared by the above method.
[0015] As another aspect of the present invention, it relates to the application of the above-mentioned suspended stable material in oil drilling cementing cement or oil drilling drilling fluid.
[0016] As another aspect of the present invention, it relates to oil drilling cementing cement or oil drilling fluid, which contains the above-mentioned suspension stabilizing material.
[0017] The suspension stabilizing material prepared by the present invention does not thicken under low temperature conditions. When tested by a thickener at a temperature below 100°C, the consistency is not higher than 30Bc. It is not diluted under high temperature conditions, and the consistency is not lower than 20Bc of the initial consistency at a temperature above 200°C. The suspension stabilizing material prepared by the present invention is used in cement slurry, has a good suspension stabilizing effect, and the density difference of the cement slurry is not greater than 0.03g / cm 3 . DETAILED DESCRIPTION
[0018] The parts referred to in this application are parts by mass unless otherwise specified.
[0019] Example 1:
[0020] Into 27.5 parts of 25 degrees Celsius water, add 40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 10 parts of N, N-dimethylacrylamide, 9 parts of methyldiallyl ammonium chloride, 7 parts of methylmaleic acid, and after fully dissolving, add 3 parts of potassium persulfate, and add 13.5 parts of sodium hydroxide to adjust the pH value, raise the temperature to 45 degrees Celsius, and keep warm for 6 hours. After the insulation is completed, cool to room temperature. The pH of the obtained polymer suspension stable material is 7.0, and the suspension stable material is too dilute, there is no obvious polymerization, and the reaction fails.
[0021] Example 2:
[0022] Into 33 parts of 25 degrees Celsius water, add 50 parts of 2-acrylamide-2-methylpropanesulfonic acid, 9 parts of N,N-dimethylacrylamide, 7 parts of methyldiallyl ammonium chloride, 5 parts of methylmaleic acid, and after fully dissolved, add 2 parts of sodium persulfate, and add 14.5 parts of sodium hydroxide to adjust the pH value, raise the temperature to 55 degrees Celsius, and keep warm for 6 hours. After the insulation is completed, cool to room temperature, and the pH of the obtained polymer suspension stable material is 6.0, and the performance evaluation is carried out:
[0023] The cement-based slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC)GWD-1S + 3.5% (BWOC)GWF-200L + 4% (BWOC)GWR-300L + 42% of distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above-mentioned polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the thickening experiment was carried out at 200 degrees Celsius and 100MPa. The experimental results showed that the slurry could not be poured into the slurry cup of the thickener and the experiment failed.
[0024] Example 3:
[0025] Into 36 parts of 25 degrees Celsius water, add 35 parts of 2-acrylamide-2-methylpropanesulfonic acid, 10 parts of N,N-dimethylacrylamide, 10 parts of methyldiallyl ammonium chloride, 6 parts of methylmaleic acid, and after fully dissolved, add 5 parts of ammonium persulfate, and add 12 parts of sodium hydroxide to adjust the pH value, raise the temperature to 70 degrees Celsius, and keep warm for 6 hours. After the insulation is completed, cool to room temperature, and the pH of the obtained polymer suspension stable material is 7.0, and the performance evaluation is carried out:
[0026] The cement-based slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC)GWD-1S + 3.5% (BWOC)GWF-200L + 4% (BWOC)GWR-300L + 42% of distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above-mentioned polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the thickening experiment was carried out at 200 degrees Celsius and 100MPa. The experimental results showed that the slurry could not be poured into the slurry cup of the thickener and the experiment failed.
[0027] Example 4:
[0028] Into 25 parts of 25 degrees Celsius water, add 30 parts of 2-acrylamide-2-methylpropanesulfonic acid, 5 parts of N, N-dimethylacrylamide, 12 parts of methyldiallyl ammonium chloride, 6.5 parts of methylmaleic acid, and after fully dissolving, add 4 parts of sodium persulfate, and add 7.5 parts of sodium hydroxide to adjust the pH value, raise the temperature to 60 degrees Celsius, and keep warm for 6 hours. After the insulation is completed, cool to room temperature. The pH of the obtained polymer suspension stable material is 5.0, and the suspension stable material is too dilute, there is no obvious polymerization, and the reaction fails.
[0029] Example 5:
[0030] Into 32 parts of 25 degrees Celsius water, add 30 parts of 2-acrylamide-2-methylpropanesulfonic acid, 6 parts of N,N-dimethylacrylamide, 15 parts of methyldiallyl ammonium chloride, 4 parts of methylmaleic acid, and after fully dissolved, add 5 parts of sodium persulfate, and add 11.5 parts of sodium hydroxide to adjust the pH value, raise the temperature to 50 degrees Celsius, and keep warm for 6 hours. After the insulation is completed, cool to room temperature, and the pH of the obtained polymer suspension stable material is 8.0, and the performance evaluation is carried out:
[0031] The cement-based slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC) GWD-1S + 3.5% (BWOC) GWF-200L + 4% (BWOC) GWR-300L + 42% distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above-mentioned polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the density of the prepared cement slurry is measured and then an evaluation experiment is conducted. The experimental conditions are 200 degrees Celsius and 100MPa. Below 100 degrees Celsius, the cement slurry consistency reading is 28Bc, and above 200 degrees Celsius, the consistency reading is 2Bc. The temperature is raised for 100 minutes under the conditions of 200 degrees Celsius and 100MPa in the thickener, and the temperature is maintained at a constant temperature for 60 minutes. After cooling, the cement slurry is taken out and the density of the cement slurry measured at room temperature is compared with the density of the previously prepared cement slurry. The difference is 0.05g / cm 3 , does not meet the requirements.
[0032] Example 6:
[0033] Into 35 parts of 25 degrees Celsius water, add 25 parts of 2-acrylamide-2-methylpropanesulfonic acid, 12 parts of N, N-dimethylacrylamide, 20 parts of methyldiallyl ammonium chloride, 13 parts of methylmaleic acid, and after fully dissolving, add 2 parts of potassium persulfate, and add 8.5 parts of sodium hydroxide to adjust the pH value, raise the temperature to 60 degrees Celsius, and keep warm for 6 hours. After the insulation is completed, cool to room temperature. The pH of the obtained polymer suspension stable material is 7.0, and the suspension stable material is too dilute, there is no obvious polymerization, and the reaction fails.
[0034] Example 7:
[0035] Into 35 parts of 25 degrees Celsius water, add 40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 8 parts of N,N-dimethylacrylamide, 13 parts of methyldiallyl ammonium chloride, 8 parts of methylmaleic acid, and after fully dissolved, add 5 parts of potassium persulfate and 13.5 parts of sodium hydroxide to adjust the pH value. The temperature is raised to 65 degrees Celsius and kept warm for 6 hours. After the insulation is completed, cool to room temperature, and the pH of the obtained polymer suspension stable material is 8.0, and the performance evaluation is carried out:
[0036] The cement-based slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC) GWD-1S + 3.5% (BWOC) GWF-200L + 4% (BWOC) GWR-300L + 42% distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above-mentioned polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the density of the prepared cement slurry is measured and then an evaluation experiment is conducted. The experimental conditions are 200 degrees Celsius and 100MPa. Below 100 degrees Celsius, the cement slurry consistency reading is 32Bc, and above 200 degrees Celsius, the consistency reading is 18Bc. The temperature is raised for 100 minutes at 200 degrees Celsius and 100MPa in the thickener, and the temperature is maintained at a constant temperature for 60 minutes. After cooling, the cement slurry is taken out and the density of the cement slurry measured at room temperature is compared with the density of the previously prepared cement slurry. The difference is 0.04g / cm 3 , does not meet the requirements.
[0037] Example 8:
[0038] Into 30 parts of 25 degrees Celsius water, add 35 parts of 2-acrylamide-2-methylpropanesulfonic acid, 8.5 parts of N,N-dimethylacrylamide, 11 parts of methyldiallyl ammonium chloride, 10 parts of methylmaleic acid, and after fully dissolved, add 3.5 parts of sodium persulfate, and add 11 parts of sodium hydroxide to adjust the pH value, raise the temperature to 55 degrees Celsius, and keep warm for 6 hours. After the insulation is completed, cool to room temperature, and the pH of the obtained polymer suspension stable material is 6.5, and the performance evaluation is carried out:
[0039] The cement-based slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC) GWD-1S + 3.5% (BWOC) GWF-200L + 4% (BWOC) GWR-300L + 42% distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above-mentioned polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the density of the prepared cement slurry is measured and then an evaluation experiment is conducted. The experimental conditions are 200 degrees Celsius and 100MPa. Below 100 degrees Celsius, the cement slurry consistency reading is 23Bc, and above 200 degrees Celsius, the consistency reading is 15Bc. The temperature is raised for 100 minutes at 200 degrees Celsius and 100MPa in the thickener, and the temperature is maintained at a constant temperature for 60 minutes. After cooling, the cement slurry is taken out and the density of the cement slurry measured at room temperature is compared with the density of the cement slurry prepared previously. The difference is 0.05g / cm 3 , does not meet the requirements.
[0040] Example 9:
[0041] Into 28 parts of 25 degrees Celsius water, add 30 parts of 2-acrylamide-2-methylpropanesulfonic acid, 4 parts of N,N-dimethylacrylamide, 20 parts of methyldiallyl ammonium chloride, 7 parts of methylmaleic acid, and after fully dissolved, add 3.5 parts of sodium persulfate, and add 9.5 parts of sodium hydroxide to adjust the pH value, raise the temperature to 50 degrees Celsius, and keep warm for 6 hours. After the insulation is completed, cool to room temperature, and the pH of the obtained polymer suspension stable material is 6.5, and the performance evaluation is carried out:
[0042] The cement slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC) GWD-1S + 3.5% (BWOC) GWF-200L + 4% (BWOC) GWR-300L + 42% distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the density of the prepared cement slurry is measured and the evaluation experiment is carried out. The experimental conditions are 200 degrees Celsius and 100MPa. Below 100 degrees Celsius, the cement slurry consistency reading is 16Bc, and above 200 degrees Celsius, the consistency reading is 4Bc. Under the conditions of 200 degrees Celsius and 100MPa in the thickener, the temperature is raised for 100 minutes, constant temperature curing is carried out for 60 minutes, and the temperature is lowered and taken out. The density of the cement slurry measured at room temperature is compared with the density of the previously prepared cement slurry. The difference is 0.06g / cm 3 , does not meet the requirements.
[0043] Example 10:
[0044] Into 28 parts of 25 degrees Celsius water, add 30 parts of 2-acrylamide-2-methylpropanesulfonic acid, 10 parts of N,N-dimethylacrylamide, 16 parts of methyldiallyl ammonium chloride, 8 parts of methylmaleic acid, and after fully dissolved, add 5 parts of ammonium persulfate, and add 8.5 parts of sodium hydroxide to adjust the pH value, raise the temperature to 50 degrees Celsius, and keep warm for 6 hours. After the insulation is completed, cool to room temperature to obtain a polymer as a suspension stabilization material, with a pH of 6.0 and a structural formula of R1-C-R2-N-R3-R4, where R1 is SO3Na; R2 is C=O; R3 is COONa; R4 is NH3Cl. Performance evaluation:
[0045] The cement-based slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC) GWD-1S + 3.5% (BWOC) GWF-200L + 4% (BWOC) GWR-300L + 42% distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above-mentioned polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the density of the prepared cement slurry is measured and then an evaluation experiment is conducted. The experimental conditions are 200 degrees Celsius and 100MPa. Below 100 degrees Celsius, the cement slurry consistency reading is 26Bc, and above 200 degrees Celsius, the consistency reading is 15Bc. The temperature is raised for 100 minutes at 200 degrees Celsius and 100MPa in the thickener, and the temperature is maintained at a constant temperature for 60 minutes. After cooling, the cement slurry is taken out and the density of the cement slurry measured at room temperature is compared with the density of the cement slurry prepared previously. The difference is 0.01g / cm 3 , which meets the requirements.
[0046] Example 11:
[0047] Into 36 parts of 25 degrees Celsius water, add 40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 5 parts of N,N-dimethylacrylamide, 9 parts of methyldiallylammonium chloride, 3 parts of methylmaleic acid, after fully dissolved, add 3 parts of potassium persulfate, and add 13.5 parts of sodium hydroxide to adjust the pH value, and keep warm at 60 degrees Celsius for 6 hours. After the insulation is completed, cool to room temperature to obtain a polymer as a suspension stabilization material, pH 7.0, the structural formula is R1-C-R2-N-R3-R4, where R1 is NH3Cl; R2 is CH2CH3; R3 is C=O; R4 is SO3Na. Performance evaluation:
[0048] The cement-based slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC) GWD-1S + 3.5% (BWOC) GWF-200L + 4% (BWOC) GWR-300L + 42% distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above-mentioned polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the density of the prepared cement slurry is measured and then an evaluation experiment is conducted. The experimental conditions are 200 degrees Celsius and 100MPa. Below 100 degrees Celsius, the cement slurry consistency reading is 18Bc, and above 200 degrees Celsius, the consistency reading is 11Bc. The temperature is raised for 100 minutes at 200 degrees Celsius and 100MPa in the thickener, and the temperature is maintained at a constant temperature for 60 minutes. After cooling, the cement slurry is taken out and the density of the cement slurry measured at room temperature is compared with the density of the previously prepared cement slurry. The difference is 0.03g / cm 3 , which meets the requirements.
[0049] Example 12:
[0050] Into 28 parts of 25 degrees Celsius water, add 30 parts of 2-acrylamide-2-methylpropanesulfonic acid, 8.5 parts of N,N-dimethylacrylamide, 17 parts of methyldiallyl ammonium chloride, 7 parts of methylmaleic acid, after fully dissolved, add 4 parts of sodium persulfate, and add 9.5 parts of sodium hydroxide to adjust the pH value, and keep warm at 50 degrees Celsius for 6 hours. After the insulation is completed, cool to room temperature to obtain a polymer as a suspension stabilization material, the pH is 6.5, and the structural formula is R1-C-R2-N-R3-R4, where R1 is CH2CH3; R2 is C=C; R3 is NH3Cl; R4 is COONa. Performance evaluation:
[0051] The cement-based slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC) GWD-1S + 3.5% (BWOC) GWF-200L + 4% (BWOC) GWR-300L + 42% distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above-mentioned polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the density of the prepared cement slurry is measured and then an evaluation experiment is conducted. The experimental conditions are 200 degrees Celsius and 100MPa. Below 100 degrees Celsius, the cement slurry consistency reading is 24Bc, and above 200 degrees Celsius, the consistency reading is 20Bc. Under the conditions of 200 degrees Celsius and 100MPa in the thickener, the temperature is raised for 100 minutes, and the temperature is maintained at a constant temperature for 60 minutes. After cooling, the cement slurry is taken out and the density of the cement slurry measured at room temperature is compared with the density of the cement slurry prepared previously. The difference is 0.02g / cm 3 , which meets the requirements.
[0052] Example 13:
[0053] In 32 parts of 25 degrees Celsius water, 35 parts of 2-acrylamide-2-methylpropanesulfonic acid, 7.5 parts of N,N-dimethylacrylamide, 11 parts of methyldiallylammonium chloride, and 4 parts of methylmaleic acid are fully dissolved, and then 4 parts of potassium persulfate are added, and 11 parts of sodium hydroxide are added to adjust the pH value, and the temperature is kept at 55 degrees Celsius for 6 hours. After the insulation is completed, it is cooled to room temperature to obtain a polymer as a suspension stabilization material with a pH of 6.5 and a structural formula of R1-C-R2-N-R3-R4, wherein R1 is COONa; R2 is NH3Cl; R3 is C=C; and R4 is SO3Na. Performance evaluation:
[0054] The cement-based slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC) GWD-1S + 3.5% (BWOC) GWF-200L + 4% (BWOC) GWR-300L + 42% distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above-mentioned polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the density of the prepared cement slurry is measured and then an evaluation experiment is conducted. The experimental conditions are 200 degrees Celsius and 100MPa. Below 100 degrees Celsius, the cement slurry consistency reading is 13Bc, and above 200 degrees Celsius, the consistency reading is 8Bc. The temperature is raised for 100 minutes at 200 degrees Celsius and 100MPa in the thickener, and the temperature is maintained at a constant temperature for 60 minutes. After cooling, the cement slurry is taken out and the density of the cement slurry measured at room temperature is compared with the density of the cement slurry prepared previously. The difference is 0.01g / cm 3 , which meets the requirements.
[0055] Example 14:
[0056] Into 34 parts of 25 degrees Celsius water, add 36 parts of 2-acrylamide-2-methylpropanesulfonic acid, 6 parts of N,N-dimethylacrylamide, 14 parts of methyldiallyl ammonium chloride, 4.5 parts of methylmaleic acid, after fully dissolved, add 3 parts of ammonium persulfate, and add 10.5 parts of sodium hydroxide to adjust the pH value, raise the temperature to 52 degrees Celsius, and keep warm for 6 hours. After the insulation is completed, cool to room temperature to obtain a polymer as a suspension stabilization material, pH 6.0, the structural formula is R1-C-R2-N-R3-R4, where R1 is NH3Cl; R2 is C=O; R3 is COONa; R4 is SO3Na. Performance evaluation:
[0057] The cement-based slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC) GWD-1S + 3.5% (BWOC) GWF-200L + 4% (BWOC) GWR-300L + 42% distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above-mentioned polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the density of the prepared cement slurry is measured and then an evaluation experiment is conducted. The experimental conditions are 200 degrees Celsius and 100MPa. Below 100 degrees Celsius, the cement slurry consistency reading is 22Bc, and above 200 degrees Celsius, the consistency reading is 13Bc. The temperature is raised for 100 minutes under the conditions of 200 degrees Celsius and 100MPa in the thickener, and the temperature is maintained at a constant temperature for 60 minutes. After cooling, the cement slurry is taken out and the density of the cement slurry measured at room temperature is compared with the density of the cement slurry prepared previously. The difference is 0.01g / cm 3 , which meets the requirements.
[0058] Example 15:
[0059] Into 30 parts of 25 degrees Celsius water, add 32 parts of 2-acrylamide-2-methylpropanesulfonic acid, 8 parts of N,N-dimethylacrylamide, 15 parts of methyldiallyl ammonium chloride, 6.5 parts of methylmaleic acid, after fully dissolved, add 5 parts of sodium persulfate, and add 11 parts of sodium hydroxide to adjust the pH value, raise the temperature to 56 degrees Celsius, and keep warm for 6 hours. After the insulation is completed, cool to room temperature to obtain a polymer as a suspension stabilization material, pH 7.0, the structural formula is R1-C-R2-N-R3-R4, where R1 is CH2CH3; R2 is NH3Cl; R3 is C=O; R4 is COONa. Performance evaluation:
[0060] The cement-based slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC) GWD-1S + 3.5% (BWOC) GWF-200L + 4% (BWOC) GWR-300L + 42% distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above-mentioned polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the density of the prepared cement slurry is measured and then an evaluation experiment is conducted. The experimental conditions are 200 degrees Celsius and 100MPa. Below 100 degrees Celsius, the cement slurry consistency reading is 16Bc, and above 200 degrees Celsius, the consistency reading is 5Bc. The temperature is raised for 100 minutes under the conditions of 200 degrees Celsius and 100MPa in the thickener, and the temperature is maintained at a constant temperature for 60 minutes. After cooling, the cement slurry is taken out and the density of the cement slurry measured at room temperature is compared with the density of the previously prepared cement slurry. The difference is 0.01g / cm 3 , which meets the requirements.
[0061] Example 16:
[0062] Into 28 parts of 25 degrees Celsius water, add 30 parts of 2-acrylamide-2-methylpropanesulfonic acid, 7 parts of N,N-dimethylacrylamide, 14 parts of methyldiallyl ammonium chloride, 3.5 parts of methylmaleic acid, and after fully dissolved, add 3 parts of potassium persulfate, and add 17.5 parts of sodium hydroxide to adjust the pH value, raise the temperature to 50 degrees Celsius, and keep warm for 6 hours. After the insulation is completed, cool to room temperature, and the pH of the obtained polymer suspension stable material is 9.0, and the performance evaluation is carried out:
[0063] The cement slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC) GWD-1S + 3.5% (BWOC) GWF-200L + 4% (BWOC) GWR-300L + 42% distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the density of the prepared cement slurry is measured and the evaluation experiment is carried out. The experimental conditions are 200 degrees Celsius and 100MPa. Below 100 degrees Celsius, the cement slurry consistency reading is 34Bc, and above 200 degrees Celsius, the consistency reading is 11Bc. Under the conditions of 200 degrees Celsius and 100MPa in the thickener, the temperature is raised for 100 minutes, constant temperature curing is carried out for 60 minutes, and the temperature is lowered and taken out. The density of the cement slurry measured at room temperature is compared with the density of the previously prepared cement slurry. The difference is 0.03g / cm 3 , does not meet the requirements.
[0064] Example 17:
[0065] Into 40 parts of 25 degrees Celsius water, add 40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 10 parts of N,N-dimethylacrylamide, 16 parts of methyldiallyl ammonium chloride, 3 parts of methylmaleic acid, and after fully dissolved, add 4 parts of sodium persulfate, and add 8 parts of sodium hydroxide to adjust the pH value, raise the temperature to 55 degrees Celsius, and keep warm for 6 hours. After the insulation is completed, cool to room temperature, and the pH of the obtained polymer suspension stable material is 4.0, and the performance evaluation is carried out:
[0066] The cement slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC) GWD-1S + 3.5% (BWOC) GWF-200L + 4% (BWOC) GWR-300L + 42% distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the density of the prepared cement slurry is measured and the evaluation experiment is carried out. The experimental conditions are 200 degrees Celsius and 100MPa. Below 100 degrees Celsius, the cement slurry consistency reading is 28Bc, and above 200 degrees Celsius, the consistency reading is 5Bc. Under the conditions of 200 degrees Celsius and 100MPa in the thickener, the temperature is raised for 100 minutes, constant temperature curing is carried out for 60 minutes, and the temperature is lowered and taken out. The density of the cement slurry measured at room temperature is compared with the density of the previously prepared cement slurry. The difference is 0.01g / cm 3 , does not meet the requirements.
[0067] Example 18:
[0068] Into 31 parts of 25 degrees Celsius water, add 35 parts of 2-acrylamide-2-methylpropanesulfonic acid, 13 parts of N,N-dimethylacrylamide, 10 parts of methyldiallyl ammonium chloride, 5 parts of methylmaleic acid, and after fully dissolved, add 6 parts of potassium persulfate, and add 11.5 parts of sodium hydroxide to adjust the pH value, raise the temperature to 60 degrees Celsius, and keep warm for 6 hours. After the insulation is completed, cool to room temperature, and the pH of the obtained polymer suspension stable material is 6.0, and the performance evaluation is carried out:
[0069] The cement slurry used is: 500g of G-grade cement + 300g of quartz sand + 10% (BWOC) GWD-1S + 3.5% (BWOC) GWF-200L + 4% (BWOC) GWR-300L + 42% distilled water (BWOC) + 1.6g of GWX-1L + 1.5% of the above polymer suspension stabilization materials. According to Chapter 4 of SY / 5546-92, the density of the prepared cement slurry is measured and the evaluation experiment is carried out. The experimental conditions are 200 degrees Celsius and 100MPa. Below 100 degrees Celsius, the cement slurry consistency reading is 35Bc, and above 200 degrees Celsius, the consistency reading is 10Bc. Under the conditions of 200 degrees Celsius and 100MPa in the thickener, the temperature is raised for 100 minutes, constant temperature curing is carried out for 60 minutes, and the temperature is lowered and taken out. The density of the cement slurry measured at room temperature is compared with the density of the previously prepared cement slurry. The difference is 0.02g / cm 3 , does not meet the requirements.
[0070] From the above examples, we can see that:
[0071] The products prepared in Examples 10-18 have good suspension stability effects, among which Examples 10-15 still maintain good suspension stability effects at a high temperature of 200 degrees. The products prepared in Examples 7-15 exhibit good high temperature resistance, among which Examples 10-15 can still achieve good suspension stability effects under high temperature conditions.
[0072] The suspension stabilizing material prepared by the present invention is a suspension stabilizing material for oil well cement slurry that does not increase viscosity at low temperature and does not dilute at high temperature, and has a structural formula of R1-C-R2-N-R3-R4, wherein R1 is SO3Na, NH3Cl, CH2CH3 or COONa; R2 is C=O, CH2CH3, C=C or NH3Cl; R3 is COONa, C=O, NH3Cl or C=C; R4 is NH3Cl, SO3Na or COONa; among R1, R2, R3 and R4, only one and only one can be NH3Cl, SO3Na or COONa. Preferably, R1 is COONa; R2 is NH3Cl; R3 is C=C; and R4 is SO3Na.
[0073] The method for preparing a suspended stable material of the present invention comprises the following steps:
[0074] Summary of Examples 7-18: After 30-40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 4-13 parts of N,N-dimethylacrylamide, 9-17 parts of methyldiallylammonium chloride and 3-8 parts of methylmaleic acid are fully dissolved in water, 3-6 parts of initiator (potassium persulfate or sodium persulfate or ammonium persulfate) are added, the pH is adjusted to 4.0-9.0, and the reaction is carried out at 50-60 degrees Celsius.
[0075] Summary of Examples 7-15: After 30-40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 4-10 parts of N,N-dimethylacrylamide, 9-17 parts of methyldiallylammonium chloride and 3-8 parts of methylmaleic acid are fully dissolved in water, 3-5 parts of initiator (potassium persulfate or sodium persulfate or ammonium persulfate) are added, the pH is adjusted to 6.0-8.0, and the reaction is carried out at 50-60 degrees Celsius.
[0076] Summary of Examples 10-18: After 30-40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 5-13 parts of N,N-dimethylacrylamide, 9-17 parts of methyldiallylammonium chloride and 3-8 parts of methylmaleic acid are fully dissolved in water, 3-6 parts of initiator (potassium persulfate or sodium persulfate or ammonium persulfate) are added, the pH is adjusted to 4.0-9.0, and the reaction is carried out at 50-60 degrees Celsius.
[0077] Summary of Examples 10-15: After 30-40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 5-10 parts of N,N-dimethylacrylamide, 9-17 parts of methyldiallylammonium chloride and 3-8 parts of methylmaleic acid are fully dissolved in water, 3-5 parts of initiator (potassium persulfate or sodium persulfate or ammonium persulfate) are added, the pH is adjusted to 6.0-7.0, and the reaction is carried out at 50-60 degrees Celsius.
[0078] The low-temperature resistant, non-viscosity-increasing, high-temperature resistant, non-dilution and ultra-high-temperature resistant oil well cement slurry suspension and stabilization material prepared by the present invention can be used for oil and gas production. Specifically, the low-temperature resistant, non-viscosity-increasing, high-temperature resistant, non-dilution and ultra-high-temperature resistant oil well cement slurry suspension and stabilization material provided by the present invention is mixed with oil well cement.
Claims
1. A suspended stable material, characterized in that: Its structural formula is R1-C-R2-N-R3-R4, wherein R1 is SO3Na, NH3Cl, CH2CH3 or COONa; R2 is C=O, CH2CH3, C=C or NH3Cl; R3 is COONa, C=O, NH3Cl or C=C; R4 is NH3Cl, SO3Na or COONa; among R1, R2, R3 and R4, one and only one is NH3Cl, SO3Na or COONa.
2. The suspended stable material according to claim 1, characterized in that: R1 is COONa; R2 is NH3Cl; R3 is C=C; R4 is SO3Na.
3. A method for preparing a suspended stable material, characterized in that: include: After 30-40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 4-13 parts of N,N-dimethylacrylamide, 9-17 parts of methyldiallylammonium chloride and 3-8 parts of methylmaleic acid are fully dissolved in water, 3-6 parts of initiator are added, the pH is adjusted to 4.0-9.0, and the reaction is carried out at 50-60 degrees Celsius.
4. The method according to claim 3, characterized in that include: After 30-40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 4-10 parts of N,N-dimethylacrylamide, 9-17 parts of methyldiallylammonium chloride and 3-8 parts of methylmaleic acid are fully dissolved in water, 3-5 parts of initiator are added, the pH is adjusted to 6.0-8.0, and the reaction is carried out at 50-60 degrees Celsius.
5. The method according to claim 3, characterized in that include: After 30-40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 5-13 parts of N,N-dimethylacrylamide, 9-17 parts of methyldiallylammonium chloride and 3-8 parts of methylmaleic acid are fully dissolved in water, 3-6 parts of initiator are added, the pH is adjusted to 4.0-9.0, and the reaction is carried out at 50-60 degrees Celsius.
6. The method of claim 3, characterized in that include: After 30-40 parts of 2-acrylamide-2-methylpropanesulfonic acid, 5-10 parts of N,N-dimethylacrylamide, 9-17 parts of methyldiallylammonium chloride and 3-8 parts of methylmaleic acid are fully dissolved in water, 3-5 parts of initiator are added, the pH is adjusted to 6.0-7.0, and the reaction is carried out at 50-60 degrees Celsius.
7. The method according to any one of claims 3 to 6, characterized in that: The initiator is potassium persulfate, sodium persulfate or ammonium persulfate.
8. A suspended stable material prepared by the method according to any one of claims 3 to 7.
9. Use of the suspended stabilizing material according to any one of claims 1, 2 or 7 in oil drilling cement or oil drilling fluid.
10. Oil drilling cement or oil drilling fluid, characterized in that: Contains the suspension stabilizing material according to any one of claims 1, 2 or 7.